Trends in Digital Health Education for Iron Supplementation During Pregnancy (2010-2025): A Bibliometric Study - Herinawati Herinawati; Ani Margawati; Sri Achadi Nugraheni; Dwi Pudjonarko (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Iron deficiency anemia is one of the major health issues that significantly impacts pregnant women, both in developing and developed countries. Interventions through health education, particularly digital-based education, are increasingly being used to improve compliance with iron supplementation. However, little is known about how global research trends on this topic have evolved over time. This study aims to analyze global research trends in scientific literature related to digital health education and mHealth interventions for iron supplementation and anemia prevention in pregnant women. To achieve this, a bibliometric analysis was conducted to map publication growth, collaboration networks, and emerging themes in the field. Methods: Data retrieval was conducted through the PubMed database using relevant keywords “Iron” AND “Anemia” AND ‘Pregnancy’ AND (“Health education” OR “Mobile health” OR “Digital health”). Articles published between 2010 and 2025 were selected. Bibliometric analysis was conducted using the VOSviewer tool to map keywords, author collaborations, and publication trends. Results: A total of 78 relevant publications were identified, with a significant increase in the past decade. Ethiopia, the USA, China, Egypt, and Indonesia were among the countries with the highest contributions. Dominant themes included mHealth and app-based approaches. Network mapping revealed major thematic clusters in technology-based interventions, compliance behavior, and pregnancy outcomes. Conclusion: Research trends indicate growing interest in the use of digital platforms to educate pregnant women about iron supplementation and anemia prevention. This reflects a paradigm shift toward more personalized and technology-based interventions. Further studies are needed to evaluate the effectiveness and sustainability of various digital intervention models.